Про lp-розв'язки різницевого рівняння з операторними коефіцієнтами - Городній, М.Ф.; Ющенко, Г.Ю. (Видавничий дім "Академперіодика" НАН України, 2008)
We obtain a criterion for solutions of a linear difference equation with operator coefficients to be p-th power summable.